On the letter þ in the Greek alphabet used in Bactria - Redondo Reyes, Pedro (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2015)
This paper reviews different theories about the origin of the grapheme þ with sibilant value in the Greek alphabet as used by the Kushan power in Hellenistic Bactria (from the fi rst century BC), to note the Bactrian language. With epigraphic and numismatic evidences, it is concluded that probably its origin lies in the modifi cation of the Greek letter rho.